The Impact of Managerial Ethics on Job Performance - A Field Study in the Industrial Companies in Dhofar Region, Sultanate of Oman - Bilal, Zaroug Osman; Kashoob, Ahamed Suhail (Journal of Economic, Administrative and Legal Sciences, 2020)
This study aimed to identify the impact of managerial ethics on job performance in the industrial companies in Dhofar region. The sample of the study consists of 120 employees who have administrative positions as per 40 questinnares per company, in Raysut Cement Company, Dhofar Power Company and Dhofar Feed Company. A total of 116 of them were valid for statistical analysis. The researchers used the analytical descriptive method since it is appropriate fot this type of the study. The most important results of the study are: There is statistically significant correlation between managerial ethics and job performance in the industrial companies in Dhofar region. In addition, the impact of organizational systems is the most managerial ethics that affects job performance, followed by organizational culture, while the effect of an individual’s ethics came last. The most important recommendations of the study are: To spread and apply the culture of managerial ethics in these institutions among all employees and striving to accelerate the adoption of ethical codes as a fundamental pillar that is considered as the main objectives of the departments of the institutions.